Alcohol consumption patterns and the risk of sarcopenia: a population-based cross-sectional study among chinese women and men from Henan province - Junya Zhai; Baihui Ma; Jin Qin; Quanjun Lyu; Pipasha Khatun; Rui Liang; Minghua Cong; Lijun Guo; Yongxia Kong (BMC, 2022)
Abstract Objectives Sarcopenia is a clinically relevant syndrome with health, social, and economic implications. Alcohol consumption is one of the risk factors for sarcopenia, but it has not been fully investigated in Chinese populations. The purpose of the present study was to assess the relationship between alcohol consumption patterns (including the volume and frequency of alcohol consumption) and sarcopenia or its elements among Chinese women and men from Henan Province. Method A cross-sectional study was designed to collect information about nutrition and health in Henan Province, China, and a total of 680 individuals were studied. Sarcopenia was defined according to the Asian Working Group for Sarcopenia (AWGS) criteria updated in 2019. Alcohol consumption was calculated in grams per day and divided into three groups. Drinking frequency was divided into four groups. We assessed the likelihood that sarcopenia was associated with drinking patterns using multiple logistic regression analysis by odds ratios (ORs) with 95% confidence interval (CIs) after multiple adjustments. Results We found that men who consumed > 25 g of ethanol per day were approximately three times more likely to have low muscle mass (OR, 3.99; 95% CI, 1.10-17.05) or low grip strength (OR, 3.39; 95% CI, 1.33-9.92) than nondrinkers after multiple adjustments. In addition, males who consumed alcohol more than 4 times per week were approximately threefold to fivefold more likely to have low muscle mass (OR, 4.99; 95% CI, 1.24-25.55) or low grip strength (OR, 3.37; 95% CI, 1.40-8.74) than nondrinkers. Unfortunately, we did not find a relationship between alcohol consumption patterns and sarcopenia or gait speed among males, and there was no association between alcohol consumption patterns and sarcopenia or any elements. Conclusion Heavy alcohol consumption and frequent drinking are important risk factors for low muscle mass and muscle strength in Chinese men from Henan province.